Diabetes mellitus exacerbates post‐myocardial infarction heart failure by reducing sarcolipin promoter methylation. (11th June 2020) - Liu, Zhongwei; Zhang, Yong; Qiu, Chuan; Zhu, Haitao; Pan, Shuo; Jia, Hao; Kang, Hongyan; Guan, Gongchang; Hui, Rutai; Zhu, Ling; Wang, Junkui
Abstract: Aims: Sarcolipin (SLN) is a key regulator of sarcoplasmic reticulum calcium‐ATPase (SERCA)2a, which handles intracellular calcium re‐uptake. This study was aimed to investigate the involvement of SLN in post‐myocardial infarction (MI) heart failure (HF) in diabetes. Methods and results: Diabetes/MI rat models were established. Altered SLN expression in diabetic hearts was screened out by microarray. A myocardiotropic viral vector was used to deliver siRNA to silence SLN. DNA methylation was evaluated by bisulfite sequencing. Cardiac functions were evaluated by invasive haemodynamic examinations. The SERCA2a activity, cytoplasmic calcium concentration ([Ca 2+ ]i ), calcium spark, and myocyte contraction were detected. Correlation between HF and diabetes was analysed in a cohort consisted of 101 ST‐segment elevated myocardial infarction (STEMI) patients between 2017 and 2019 [53.54 ± 4.64 years old; 61.4% male gender; HbA1c% 6.15 ± 2.00; and left ventricular ejection fraction (LVEF%) 40.64 ± 3.20%]. SLN expression was evaluated in left ventricular tissue sample from six STEMI patients complicated with diabetes and six STEMI patients without diabetes. Expressions of DNA methyltransferase 1a and DNA methyltransferase 3 were reduced in diabetic hearts, leading to down‐regulation of SLN promoter methylation, resulting in increased SLN expression in rats. Impaired heart systolic functions were found in experimental diabetic MI rats, which were attenuated by SLN silencing. SERCA2a activity reduction and [Ca 2+ ]i elevation were attenuated by SLN silencing in diabetic animal hearts and high‐glucose incubated primary myocytes. SLN silencing suppressed calcium sparks and improved contraction and sarcoplasmic reticulum calcium re‐uptake in high‐glucose incubated primary myocytes. Expression of SLN was up‐regulated in LV sampled from STEMI patients complicated with diabetes compared with non‐diabetic ones ( P  < 0.05). LVEF% was reduced in STEMI patients complicated with diabetes compared with non‐diabetic ones ( P  < 0.01). HbA1c% and LVEF% was related ( r  = −0.218, P  = 0.028). Increased HbA1c% was correlated with reduced LVEF% after adjustment for age, sex, body mass index, cigarette smoking, creatinine, UA, low density lipoprotein, K +, Na +, and troponin I (adjusted odds ration = 0.75, 95% confidence interval 0.62–0.90, P  = 0.002). Conclusions: Diabetes increases the vulnerability of STEMI patients to post‐MI HF by down‐regulating SLN promoter methylation, which further regulates SERCA2a activity via increasing cardiac SLN expression.